2007
DOI: 10.1677/joe-07-0440
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced regulation of steroidogenic acute regulatory protein expression in head kidney of Gilthead seabream (Sparus aurata)

Abstract: Steroidogenic acute regulatory protein (StAR) transfers cholesterol over the inner mitochondrial membrane. In mammals, StAR controls this rate-limiting step of steroidogenesis, but its expression and regulation has not been well explored in fish. The present work investigates StAR mRNA expression in the head kidney of the gilthead seabream (Sparus aurata) under different stressors. We have cloned the StAR cDNA (1461 bp) in seabream (accession number EF640987), which has an open reading frame of 861 nucleotides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 64 publications
3
28
1
Order By: Relevance
“…In addition, ACTH receptors have been found in mammalian leukocyte populations, where they contribute to modulate immune responses [53,54]. The ACTH concentration used in the present study (150 ng mL À1 ) has been shown to be effective in trout [55] and in seabream head kidney preparations, where ACTH exerts its effects through its specific receptor, which can be blocked using a specific antagonist, as we previously reported [44]. ACTH binds to MC2 receptors in the head kidney and increases cortisol production in steroidogenic cells, among other functions.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…In addition, ACTH receptors have been found in mammalian leukocyte populations, where they contribute to modulate immune responses [53,54]. The ACTH concentration used in the present study (150 ng mL À1 ) has been shown to be effective in trout [55] and in seabream head kidney preparations, where ACTH exerts its effects through its specific receptor, which can be blocked using a specific antagonist, as we previously reported [44]. ACTH binds to MC2 receptors in the head kidney and increases cortisol production in steroidogenic cells, among other functions.…”
Section: Discussionsupporting
confidence: 56%
“…Thus, it is likely that in vivo immunological responses to stress are dependent on the actions of various hormones, their interactions with each other, with immunocompetent cells as well as with other endogenous factors, such as cytokines. To further study the effects of stress hormones without all these interactions, we have used an in vitro model of seabream head kidney, which has been described for different fish species and has revealed as an useful tool in which to study the ''intraadrenal'' interactions among the different cell types of the tissue with a single preparation [44,46,47]. The aim of our study was to use this model to investigate the interactions of adrenaline and cortisol (hormones related to stress and secreted in the head kidney) and the pituitary hormone ACTH on the expression of cytokines in the seabream head kidney.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fish, several studies have shown a similar bi-directional communication between HPI-Axis and cytokines (Tort 2011). Holland et al (2002 showed that recombinant IL-1injection raises cortisol levels, and injection of lipopolysaccharide (LPS) raised plasma cortisol in yellow perch (Haukenes and Barton 2004) and promoted StAR HK expression in gilt-head bream (Castillo et al 2008). Similar an injection of LPS both in sea bream and trout have shown to promote increased cortisol secretion and increased cortisol receptor expression in most tissues, 6 to 72 h after the initial injection (Acerete et al 2007).…”
Section: Discussionmentioning
confidence: 99%